An Overview of the Use of Mechanical Turk in Behavioral Sciences: Implications for Social Work. (July 2016) - Chan, Chitat; Holosko, Michael J.
Crowdsourcing is a process in which a firm parcels out work to a "crowd" and offers payment for anyone within the crowd who completes the task determined by that firm. A growing number of behavioral scientists have begun using the Mechanical Turk (MTurk) to facilitate their research and practice, but there is apparently not one academic study in social work reporting the use of crowdsourcing tools. Social work professionals have the responsibility to use research findings to improve practice, policy, and social service delivery. This article aims to (i) provide an overview of MTurk; (ii) review specific uses of MTurk in business, psychology, health care, and education; and (iii) discuss the possible applications of MTurk for social work.